Calculate the Thermal Properties of (S2F2) Using Semi-empirical Quantum Mechanics (MNDO / PM3) - Resan, Nada J.; Abdullhussein, Ruaa S.; Haider, Haider M.J (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2022)
In this paper, thermal properties were performed by using semi-empirical theoretical calculations to study the molecular structure of a nonlinear molecular system, the (S2F2) molecule in the infrared region, by using semi-empirical quantum programs in the (MNDO / PM3) method. This study is under the condition of obtaining the stable structure of the molecule in which the molecule obtains the minimum value of the total energy. The thermodynamic properties were also calculated, including the heat of formation, whose value was (-61.002kcal / mol),  the entropy and its value (78.2916 cal / mol.k), as well as the heat capacity  (15.9454 cal / mol.k) and the enthalpy (3763.434 cal /mol),  Gibbs Free Energy, it was valued at (-19567.5 cal / mol), these values ​​were taken at the standard temperature 298 k, withdrawing these relationships in graphs and showing the changes in the state That the molecule passes through, and comparing these values with the experimental results.